دور حاضنات االاعمال في دعم و تنمية االمؤسسات الناشئة - زهاني يحي - - هدور نعيمة (جامعة المسيلة, 2024)
حاضنات األعمال تعد من أهم اآلليات المستحدثة في الجزائر لدعم و تنمية المؤسسات الناشئة و تحقيق التنمية في شتى المجاالت و ترقية و تطوير االقتصاد الوطني , تم استحداثها بموجب المرسوم التنفيذي رقم 254-20 الذي تضمن اال الشروط التي يجب أن تتوفر في كل من قدم طلب للحصول على عالمة "مؤسسة ناشئة" و"مشروع مبتكر" و"حاضنة أعمال" و إجراءات الحصول على العالمة و حدد الخدمات التي تقدمها للمؤسسات الناشئة . كما البد من أن تتوافر عدة شروط أو عوامل تعتبر كمحفزات للحاضنة للقيام بدورها على أكمل وجه لعل أهمها وفرة التمويل و توفير مبنى مخصص للحاضنة لتمكينها من استضافة المشاريع و دعمها و اضهار فاعليتها , حيث تظهر فاعلية حاضنة االعمال من خالل عدد المؤسسات الناشئة التي تخرجت منها و تطورت لتصبح شركة تجارية ذات مكانة في السوق الوطنية و العالمية و من خالل كفاءة مديرها و قدرتها على الحصول على التمويل . من خالل ما سبق يالحظ أن حاضنات األعمال في الجزائر ال تمتلك تلك الفاعلية الكبيرة التي تمتلكها حاضنات األعمال في الدول المتطورة و النامية األخر وذلك يرجع لتأخر األعتماد على هذه اآللية و عديد المشاكل التي تعترضها و لعل ابرزها مشكل البيروقراطية و قلة النصوص التشريعية التي تنظم هذا القطاع 76 Abstract Business incubators are among the most innovative mechanisms in Algeria for supporting and developing startups, achieving development across various fields, and promoting and developing the national economy. They were established by Executive Decree No. 20-254, which outlines the conditions that must be met by anyone applying for the "Startup" and "Innovative Project" labels, as well as "Business Incubator," and the procedures for obtaining these labels. It also specifies the services provided to startups. There are several conditions or factors that serve as incentives for the incubator to perform its role effectively. The most important include the availability of funding and a dedicated building for the incubator to enable it to host and support projects and demonstrate its effectiveness. The effectiveness of a business incubator is reflected in the number of startups that graduate from it and develop into established companies with a significant presence in both the national and international markets, as well as through the competence of its manager and its ability to secure funding. Based on the above, it is noted that business incubators in Algeria do not possess the high level of effectiveness found in those in developed and other developing countries. This is due to the delayed adoption of this mechanism and numerous challenges, notably bureaucracy and the lack of legislative texts regulating this sector.